IMPULSE: A scalable algorithm for design of minimum specific absorption rate parallel transmit RF pulses. Issue 4 (13th November 2018) - Pendse, Mihir; Stara, Riccardo; Mehdi Khalighi, Mohammad; Rutt, Brian
Abstract : Purpose: Managing local specific absorption rate (SAR) in parallel transmission requires ensuring that the peak SAR over a large number of voxels (> 10 5 ) is below the regulatory limit. The safety risk to the patient depends on cumulative (not instantaneous) SAR thus making a joint design of all RF pulses in a sequence desirable. We propose the Iterative Minimization Procedure with Uncompressed Local SAR Estimate (IMPULSE), an efficient optimization formulation and algorithm that can handle uncompressed SAR matrices and optimize pulses for all slices jointly within a practical time frame. Theory and Methods: IMPULSE optimizes parallel transmit pulses for small‐tip‐angle slice selective excitation to minimize a single cost function incorporating multiple quantities (local SAR, global SAR, and per‐channel power) averaged over the entire multislice scan subject to a strict constraint on excitation accuracy. Pulses for an 8‐channel 7T head coil were designed with IMPULSE and compared with pulses designed using generic optimization algorithms and VOPs to assess the computation time and SAR performance benefits. Results: IMPULSE achieves lower SAR and shorter computation time compared with a VOP approach. Compared with the generic sequential quadratic programming algorithm, computation time is reduced by a factor of 5‐6 by using IMPULSE. Using as many as 6 million local SAR terms, up to 120 slices can be designed jointly with IMPULSE within 45 s. Conclusions: IMPULSE can handle significantly larger number of SAR matrices and slices than conventional optimization algorithms, enabling the use of uncompressed or partially compressed SAR matrices to design pulses for a multislice scan in a practical time frame.